Sensitivity of the Puget Sound ecosystem to ocean acidification using mineralogy and taxonomy as indicators (NCEI Accession 0169109) ... - Busch, D. Shallin; McElhany, Paul (NOAA National Centers for Environmental Information, 2017)
This dataset contains a number of files related to a project that characterizes the sensitivity of the Puget Sound ecosystem to ocean acidification by estimating, at a number of taxonomic levels, the direct sensitivity of its species. It includes a database of marine species in Puget Sound (.csv) with estimates of species mineralogy in the adult and early life stages, and a list (.docx) of references called to in the database. It also includes a list (.csv) of species in the Puget Sound that are also included in a second database that collects the results of studies on the sensitivity of temperate marine species to ocean acidification (Busch and McElhany 2016, https://doi.org/10.1371/journal.pone.0160669). This latter database (.csv) is presented in an abbreviated format here including only species taxonomy, reference for the manuscript presenting data on the species, scores estimating the relevance of these studies to understanding the sensitivity of Puget Sound species to ocean acidification, and the ...